When Comorbidity, Aging, and Complexity of Primary Care Meet: Development and Validation of the Geriatric CompleXity of Care Index. Issue 4 (21st March 2013) - Min, Lillian; Wenger, Neil; Walling, Anne M.; Blaum, Caroline; Cigolle, Christine; Ganz, David A.; Reuben, David; Shekelle, Paul; Roth, Carol; Kerr, Eve A.
<x xml:space="preserve">Abstract</x> Objectives To develop and validate the Geriatric CompleXity of Care Index (GXI), a comorbidity index of medical, geriatric, and psychosocial conditions that addresses disease severity and intensity of ambulatory care for older adults with chronic conditions. Design Development phase: variable selection and rating by clinician panel. Validation phase: medical record review and secondary data analysis. Setting Assessing the Care of Vulnerable Elders‐2 study. Participants Six hundred forty‐four older (≥75) individuals receiving ambulatory care. Measures Development: 32 conditions categorized according to severity, resulting in 117 GXI variables. A panel of clinicians rated each GXI variable with respect to the added difficulty of providing primary care for an individual with that condition. Validation: Modified versions of previously validated comorbidity measures (simple count, Charlson, Medicare Hierarchical Condition Category), longitudinal clinical outcomes (functional decline, survival), intensity of ambulatory care (primary, specialty care visits, polypharmacy, number of eligible quality indicators (NQI)) over 1 year of care. Results The most‐morbid individuals (according to quintiles of GXI) had more visits (7.0 vs 3.7 primary care, 6.2 vs 2.4 specialist), polypharmacy (14.3% vs 0% had ≥14 medications), and greater NQI (33 vs 25) than the least‐morbid individuals. Of the four comorbidity measures, the GXI was the strongest predictor of primary care visits, polypharmacy, and NQI (P < .001, controlling for age, sex, function‐based vulnerability). Conclusion Older adults with complex care needs, as measured by the GXI, have healthcare needs above what previously employed comorbidity measures captured. Healthcare systems could use the GXI to identify the most complex elderly adults and appropriately reimburse primary providers caring for older adults with the most complex care needs for providing additional visits and coordination of care.